(untitled) (Iraqi Journal of Medical Sciences, 2016)
Hydatid disease is one of the commonest zoonotic diseases. It is caused by the larval cyst of Echinococcusgranulosus and result in the most severe form of cetodiases in man. The hydatid disease is endemic in some Mediterranean countries, the Middle East, the South America, and South Africa and Oceania. The combination of imaging and serology usually enables diagnosis. We report a case of single and giant hydatid cyst in an unusual site (retroperitoneal region) which is very rare and also in a five-year old child which is unlikely to happen at such age with this big size. Keywords: Hydatid disease, retoperitoneal region.